Occlusal characteristics including spacing among preschool children: a cross-sectional study - Pradhan, Megha; Dhital, Shweta; Dahal, Sirjana; Joshi, Ujjwal; Sherchan, Prabesh; Pokhrel, Prafen (Journal of Chitwan Medical College, 2019)
Background: Understanding the association between morphological aspects in the primary dentition and its transition to the permanent dentition provides the possibility of predicting the final permanent occlusion. Study on the occlusal characteristics in deciduous dentition in Nepalese population is limited. This study was aimed to assess the occlusal characteristics and spacing in primary dentition in preschool children. Methods: The cross-sectional study was conducted among 432 preschool children around Kathmandu valley after getting permission from Institutional Review Committee of Kathmandu Medical College and Teaching Hospital. Each child fulfilling the inclusion criteria was enrolled on the study only after their assent and their parent’s consent. The primary molar relation, canine relation, overjet, overbite was assessed using Foster and Hamilton criteria with the teeth in centric occlusion. Primate and physiological spaces were assessed. Data was collected and analysis was done in SPSS version 16. Results: Among the participants, (51.9%) were male and (48.1%) female. Primate spaces was seen to be absent on157 (36.3%) children. Physiological space was seen among 190 (44%) children. Flush terminal plane molar relationship was more prevalent among 294 (68%) children. Class I canine relationship was found in 257(59.5%) children. Ideal overjet was seen in 333 (77.1%) children and ideal overbite was seen among 337(78%) children. Conclusions: Favorable characteristics traits were seen in the studied population yet longitudinal studies are recommended to predict the possible outcome in permanent dentition.